Relation of sputum neutrophilia to the development of chronic lung allograft dysfunction after lung transplantation. Issue 3 (5th January 2021) - Sikkeland, Liv Ingunn Bjoner; Durheim, Michael Thomas; Riste, Tonje Bøyum; Kongerud, Johny; Alexis, Neil E.; Holm, Are Martin
Abstract: Chronic lung allograft dysfunction (CLAD) is a serious complication after lung transplantation (LuTx) and is associated with elevated proportions of neutrophils in bronchoalveolar lavage (BAL). Induced sputum is a less‐invasive sampling method than BAL and assesses markers of inflammation on the surfaces of large central airways. We wanted to examine whether % neutrophil levels in induced sputum were elevated prior to CLAD diagnosis among LuTx recipients, and whether sputum markers of inflammation can be used as a tool for predicting the development of CLAD. Induced sputum samples were collected at 1, 3, 6, 12, and 24 months post‐LuTx in 36 patients with a history of COPD or pulmonary fibrosis, and of these, 16 developed CLAD either during or after the sputum surveillance period. At 2 years, median (IQR) % neutrophils in induced sputum were significantly higher among patients with CLAD compared with those without CLAD [73 (52‐80) % vs 59 (41‐76) %, p  = .01]. Interestingly, we found a significant increase in the rate of change in % neutrophils beginning at 90 days preceding the diagnosis of CLAD. This suggests using sputum neutrophil percentage as a surveillance modality for monitoring lung allograft function after LuTx.